RETRACTED: Kesesuaian Fiqih Talak Syi’ah Imamiyyah dengan Aturan Perkawinan Di Indonesia - Thoriq Ulumuddin; M. Habibi (Universitas Islam Negeri Raden Fatah Palembang, 2022)
Abstract: One of Laws of Marriage in Indonesia is regulated by Presidential Instruction No.1 in 1991 regarding Islamic Law Compilation (KHI) where it does not fully agree with opinions of the scholar (‘Ulama) of Madzhab al-Arba'ah Sunni as contained in articles 115, 129, 130 and 134 because these articles have never been found in view of Madzhab al -Arba'ah Sunni and even tends to be counter. Therefore, many religious institutions or Islamic organizations have issued